Does the quality of governance matter for equity market risk? Evidence from emerging and developed equity markets - Low, Soo-Wah; Tee, Lain-Tze; Kew, Si-Roei (Journal of Business Economics and Management, 2014)
This paper examines the relation between country-level governance and cross-country differences in equity market risk by employing panel data regressions. For emerging markets, we find consistent evidence that governance quality of various dimensions is negatively related to equity market risk. On the contrary, for developed markets, the results show that there is generally little or no relation between governance quality and equity market risk. The results provide practical implication to policy makers of emerging markets by highlighting the relevant governance dimensions that constitute important drivers of stock market risk. The findings have academic implication in the context of equilibrium pricing of stock market in emerging market.